Modern views for the treatment of placental dysfunction in pregnant after IVF - О. В. Кравченко (Publishing House TRILIST, 2018)
With the introduction of in vitro fertilization, the quantity of problems associated with the high incidence of obstetric and perinatal pathology in women with induced pregnancy have increased. The purpose of the study was to evaluate the effectiveness of complex therapy aimed at the prevention and treatment of placental dysfunction in pregnant women after in vitro fertilization. Under observation there were 23 pregnant women after in vitro fertilization (main group) and 20 women with physiological pregnancy (control group). Exclusion criteria from the study were multiple pregnancy, abnormal development of the female genital organs, severe extragenital pathology in mother, congenital abnormalities of the fetus. Considering the decrease in chorion vascularization, its hypoplasia, as well as hemodynamic disturbances in the myometrium at the end of the first trimester of gestation in pregnant women after IVF, it can be said with certainty that in addition to hormonal support in patients with induced pregnancy, therapy is aimed at normalizing uterine-chorial blood flow, restoration of effective embryo-chorial relationships. To this end, we have proposed a complex of therapeutic agents, which includes venotonic Normoven 1 tablet 2 times a day and Magnicum1 tablet 3 times a day. In order to activate metabolic processes in the body, the drug Arthiol was administered of 600-1200 mg per day before a meal. The treatment was performed twice at 10-12 and 15-18 weeks of gestation. The proposed complex of therapeutic agents helps to normalize uterine-chorial blood flow, restore effective embryo-chorial relationships, and significantly reduces the incidence of placental dysfunction in the future.